Serine/Glycine Lipid Recovery in Lipid Extracts From Healthy and Diseased Dental Samples: Relationship to Chronic Periodontitis - Nichols, Frank C.; Bhuse, Kruttika; Clark, Robert B.; Provatas, Anthony A.; Carrington, Elena; Wang, Yu-Hsiung; Zhu, Qiang; Davey, Mary E.; Dewhirst, Floyd E. (Frontiers in Oral Health, 2021)
Toll-like receptor 2 (TLR2) activation has been implicated in the pathogenesis of periodontal disease but the identity of the TLR2 agonists has been an evolving story. The serine/glycine lipids produced by Porphyromonas gingivalis are reported to engage human TLR2 and will promote the production of potent pro-inflammatory cytokines. This investigation compared the recovery of serine/glycine lipids in periodontal organisms, teeth, subgingival calculus, subgingival plaque, and gingival tissues, either from healthy sites or periodontally diseased sites. Lipids were extracted using the phospholipid extraction procedure of Bligh and Dyer and were analyzed using liquid chromatography/mass spectrometry for all serine/glycine lipid classes identified to date in P. gingivalis. Two serine/glycine lipid classes, Lipid 567 and Lipid 1256, were the dominant serine/glycine lipids recovered from oral Bacteroidetes bacteria and from subgingival calculus samples or diseased teeth. Lipid 1256 was the most abundant serine/glycine lipid class in lipid extracts from P. gingivalis, Tannerella forsythia, and Prevotella intermedia whereas Lipid 567 was the most abundant serine/glycine lipid class recovered in Capnocytophaga species and Porphyromonas endodontalis. Serine/glycine lipids were not detected in lipid extracts from Treponema denticola, Aggregatibacter actinomycetemcomitans, or Fusobacterium nucleatum. Lipid 1256 was detected more frequently and at a significantly higher mean level in periodontitis tissue samples compared with healthy/gingivitis tissue samples. By contrast, Lipid 567 levels were essentially identical. This report shows that members of the Bacteroidetes phylum common to periodontal disease sites produce Lipid 567 and Lipid 1256, and these lipids are prevalent in lipid extracts from subgingival calculus and from periodontally diseased teeth and diseased gingival tissues.